1990
DOI: 10.1136/gut.31.5.514
|View full text |Cite
|
Sign up to set email alerts
|

Abolition by omeprazole of aspirin induced gastric mucosal injury in man.

Abstract: This study investigates whether aspirin injury to the human gastric mucosa can be prevented by profound acid suppression with omeprazole, in a randomised, double blind, crossover design according to latin square. It was concluded that profound acid suppression can prevent aspirin induced gastric mucosal injury in normal subjects. This approach may prevent the development of peptic ulcers and their complications in patients taking aspirin and other non-steroidal anti-inflammatory drugs.Aspirin and non-steroidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…These results extend the results of other, smaller and/or non-controlled studies of primary prevention by PPIs of short-term non-selective NSAID-related GI side effects [31]. Most such studies have utilized aspirin (ASA) [32][33][34][35][36][37][38][39]. The available evidence suggests that OMP results in an approximately 75% decrease in the incidence of endoscopic lesions related to either low-dose or antiinflammatory dose of ASA daily [32,37].…”
Section: Discussionsupporting
confidence: 64%
“…These results extend the results of other, smaller and/or non-controlled studies of primary prevention by PPIs of short-term non-selective NSAID-related GI side effects [31]. Most such studies have utilized aspirin (ASA) [32][33][34][35][36][37][38][39]. The available evidence suggests that OMP results in an approximately 75% decrease in the incidence of endoscopic lesions related to either low-dose or antiinflammatory dose of ASA daily [32,37].…”
Section: Discussionsupporting
confidence: 64%
“…At least 2 randomized, controlled trials have demonstrated that mucosal gastric injury from aspirin at similar or higher doses than those used in our study can be abolished by adjuvant use of the proton pump inhibitor omeprazole. 40,41 We therefore take the position that the gastrointestinal bleeding risk of high-dose aspirin is acceptable, provided that a proton pump inhibitor is additionally prescribed. This was supported by the fact that no serious gastric or bleeding events requiring medical attention were observed in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…41 Additionally, one small trial of short duration found that omeprazole 20 -40 mg/day decreased the incidence of high-dose aspirin-induced gastric mucosal bleeding compared with placebo. 39 Lai et al 42 evaluated the efficacy of lansoprazole in preventing recurrent ulcer complications in 123 patients with eradicated H. pylori infection and a previous history of ulcer complications due to low-dose aspirin (100 mg/day). Patients continued on aspirin 100 mg/day and received either lansoprazole 30 mg/day or placebo for 12 months.…”
Section: Proton-pump Inhibitorsmentioning
confidence: 99%